Heterotopic ossification – A rare donor site complication after iliac crest free flap - Filipa Poleri; Jorge Correia-Pinto; Larissa Lanzaro; Rui Casimiro; Bruno Morgado; Horácio Costa (JPRAS Open, 2024)
Summary: Iliac crest free flap is still essential as a source of vascularized bone tissue, having a definite role in osseous reconstruction of the face and other small bone defects. Some of its drawbacks include laborious dissection and donor site morbidity. We report a case of a patient that presented to our follow-up consultation ten years after iliac crest free flap harvest with new complaints of pain, gait disturbance and swelling in the right hip. Imaging exams revealed a heterotopic bone formation and helped with the diagnosis of heterotopic ossification (HO) of the right iliacus bone. Surgical intervention was needed for debridement of the heterotopic bone, with resolution of the symptoms. To our knowledge, this is the first report of HO after iliac crest free flap harvest. This rare condition adds to an already well-known number of donor zone complications of this flap. Plastic surgeons should be aware of this complication, as it can cause disability many years after the original surgery.